EFFECTS OF SHEXIANGBAOXIN PILLS ON THE EXPRESSION OF CARDIAC α1- AND β-ADRENERGIC RECEPTOR SUBTYPES IN RAT HEARTS WITH HEART FAILURE INDUCED BY MYOCARDIAL INFARCTION. (8th October 2012) - Yan-fang, Li; Fang-fang, Cao; Fei, Liu; Zhi-li, Jiang; Yanfang, Li
Abstract : Objectives: Chronic heart failure (CHF) had been characterised as an activated sympathetic system leading to the alteration of adrenergic receptor (AR) levels in the heart. Thus far, not much research has been done with regard to traditional Chinese medical treatment for CHF. We investigated the effect of Shexiangbaoxin pills (SXBXP) on the function of the heart and the expression of a1 -AR and b-AR subtypes in the messenger RNA (mRNA) levels and protein levels of non-infarction left ventricular tissue from rats with CHF induced by myocardial infarction. Methods: Models of CHF were established by left anterior descending coronary artery ligature. Fifty-four Wistar rats were randomly divided into five groups: normal control group (group A), sham operation group (group B), CHF model group (group C), positive medicine control group (group D), and small-dose SXBXP group (group E) and large-dose SXBXP group (group F), deployed intragastrically. Cardiac function was examined by echocardiography before and after therapy; mRNA expressed levels were measured by semiquantitative reverse transcription polymerase chain reaction (RT-PCR) for b1 -AR, b2 -AR, b3 -AR, a1A -AR, a1B -AR, and a1D -AR; protein levels were measured by western blotting analysis for b1 -AR, b2 -AR, a1A -AR, a1B -AR, and a1D -AR in non-infarction left ventricular tissue. Results: There was no significant difference in the left ventricular ejection fraction (LVEF) between groups A and B. Compared to group B, LVEF of groups C, D, E, and F were significantly decreased (p<0.01) before therapy. After therapy, compared to group C, LVEF of group F was significantly improved (p<0.05). Compared to group B, b1 -AR and a1B -AR expressed levels were markedly decreased (p<0.05), a1A -AR and b3 -AR were significantly increased (p<0.01) in group C, and in both mRNA and protein expressed levels b2 -AR had no significant difference between groups B and C (p>0.05). a1D -AR mRNA levels were unchanged in each group (p>0.05), but a1D -AR protein level was significantly decreased in group C (p<0.05). After treatment, compared to group C, mRNA levels of b1 -AR and a1B -AR were significantly increased (p<0.05 and P<0.01), and a1A -AR was markedly decreased in groups D, E, and F (p<0.05). b3 -AR level significantly declined in both groups D and F (p<0.01), but b2 -AR and a1D -AR expressed levels remained unchanged in each group (p>0.05). Protein levels, compared to group C, b1 -AR was significantly increased (p<0.01, p<0.05, and p<0.01) and a1A -AR was markedly decreased in groups D, E, and F (p<0.05, p<0.01, and p<0.01). b2 -AR expressed level was significantly increased in group F (p<0.05). a1B -AR expressed level was significantly increased in both groups E and F (p<0.05), and a1D -AR was remarkably increased in both groups D and F (p<0.05). Conclusions: After SXBXP treatment, LVEF was increased and cardiac function was significantly ameliorated in rats with CHF. The therapeutic effect of SXBXP may be related to better blood supply for myocardium and up-regulation of b1 -AR and a1B -AR, and down-regulation of a1A -AR and b3 -AR. The results show that SXBXP can be used in treatment of CHF and the therapeutic effect of large-dose SXBXP is superior to small-dose SXBXP.